2019
DOI: 10.1148/radiol.2019190559
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Function with MRI Enables Prediction of Cardiovascular Events after Myocardial Infarction: Insights from the AIDA STEMI and TATORT NSTEMI Trials

Abstract: CARDIAC IMAGINGL eft ventricular (LV) ejection fraction (EF) is used to assess systolic myocardial function after acute myocardial infarction (AMI), and reduced LV EF is associated with adverse cardiovascular events (1). Risk stratification can be optimized by assessing myocardial ventricular strain with incremental value over LV EF, suggesting an important role of ventricular function imaging in patients with recent AMI (2,3).The importance of left atrial (LA) function and structure is increasingly recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 35 publications
5
63
0
1
Order By: Relevance
“…The larger analysis by Ledwoch and colleagues including 684 STEMI patients measured LA function only by ejection fraction and could find an independent association between LA ejection fraction and adverse clinical events; however, the prognostic value of LA ejection fraction was not incremental to LV ejection fraction [48]. Hence, more comprehensive approaches of LA function assessment have been developed and tested [49,50]. Comparable with the LV, LA strain analysis has become available for CMR enabling a comprehensive evaluation of the complex function of the LA, comprising reservoir function, conduit function and contractile booster pump function [49].…”
Section: Atrial Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger analysis by Ledwoch and colleagues including 684 STEMI patients measured LA function only by ejection fraction and could find an independent association between LA ejection fraction and adverse clinical events; however, the prognostic value of LA ejection fraction was not incremental to LV ejection fraction [48]. Hence, more comprehensive approaches of LA function assessment have been developed and tested [49,50]. Comparable with the LV, LA strain analysis has become available for CMR enabling a comprehensive evaluation of the complex function of the LA, comprising reservoir function, conduit function and contractile booster pump function [49].…”
Section: Atrial Functionmentioning
confidence: 99%
“…Comparable with the LV, LA strain analysis has become available for CMR enabling a comprehensive evaluation of the complex function of the LA, comprising reservoir function, conduit function and contractile booster pump function [49]. In a large multicenter CMR study including 1046 patients with STEMI and non-STEMI, Schuster et al evaluated the prognostic implications of LA function parameters as determined by feature-tracking (LA reservoir function peak systolic strain, LA conduit strain, and LA booster pump function active strain) [50]. All three atrial strain measures showed strong associations with MACE, whereas only LA peak reservoir strain emerged as an independent and incremental prognosis marker, above and beyond LV ejection fraction, infarct severity markers, and even LV global longitudinal strain [50].…”
Section: Atrial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Another recent trial demonstrated quite convincingly that left atrial function yielded incremental prognostic value above left ventricular ejection fraction in patients after myocardial infarction. 9 The myosin activator danicamtiv acts similarly on both ventricular and atrial myocardium, although myosin isoforms differ in both chambers. Of course, the effects on diastolic function, likely associated with prolonged cross-bridge attachment and also reflected by prolonged systolic ejection time, are a concern.…”
Section: This Article Refers To 'Effects Of Danicamtiv a Novel Cardimentioning
confidence: 99%
“…The increase in left atrial function is particularly interesting since it was recently shown to be an independent predictor of cardiac performance and outcomes 7,8 . Another recent trial demonstrated quite convincingly that left atrial function yielded incremental prognostic value above left ventricular ejection fraction in patients after myocardial infarction 9 . The myosin activator danicamtiv acts similarly on both ventricular and atrial myocardium, although myosin isoforms differ in both chambers.…”
Section: Figurementioning
confidence: 99%